Effects of a participatory-art based intervention on holistic health outcomes of Singapore older community dwellers: the Singapore a-health study - Ho, Reen Wan Li (Nanyang Technological University, 2022)
The rapid ageing of populations entails high costs for societies and calls for effective public health interventions to mitigate its impacts. The Singapore A-Health Study constitutes part of an international randomised controlled trial to standardise a robust framework of art intervention for health enhancement in older adults. Using a mixed methods analysis on a subsample, this paper examines the effect of the participatory arts intervention on holistic health outcomes of Singapore older community dwellers. Participants aged 60 and above were openly recruited (N = 62) and randomly assigned into the intervention (N = 31) or control (N = 31) group. The intervention group attended 12 weekly workshops at the National Gallery Singapore, comprising museum tours and art-making, while the control group attended none. Frailty, wellbeing and quality of life were assessed for all participants at four regular intervals, including at baseline before the randomised allocation. The intervention group additionally participated in a focus group discussion at the end of the intervention. Intervention group participants were hypothesised to experience unique improvements in frailty, wellbeing and quality of life over the 12 weeks. Linear mixed-effect models did not find quantitative evidence for intervention effects, though a thematic analysis uncovered four themes pointing to benefits of the intervention: promoting cognitive stimulation, enhancing perceived self-efficacy, enabling social involvement and fostering art appreciation. These themes were discussed on their holistic health benefits and health-transforming potential for participants. Overall, findings point to the potential of participatory arts interventions in shaping healthy ageing programmes in Singapore.